2021
DOI: 10.1007/s00204-021-03182-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the in vitro steatotic mixture effects of similarly and dissimilarly acting test compounds using an adverse outcome pathway-based approach

Abstract: Within the EuroMix project, we have previously developed an adverse outcome pathway (AOP)-based in vitro assay toolbox to investigate the combined effects of liver steatosis-inducing compounds in human HepaRG hepatocarcinoma cells. In this study, we applied the toolbox to further investigate mixture effects of combinations, featuring either similarly acting or dissimilarly acting substances. The valproic acid structural analogs 2-propylheptanoic acid (PHP) and 2-propylhexanoic acid (PHX) were chosen for establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This first AOP was taken as a starting point, and other NRs were incorporated as MIEs as well [88][89][90][91][92][93][94]. Presently, most, if not all AOPs for steatosis in AOP-Wiki identify a NR or another TF as the MIE.…”
Section: Consistency Of Identified Difld Mechanisms With Current Adve...mentioning
confidence: 99%
“…This first AOP was taken as a starting point, and other NRs were incorporated as MIEs as well [88][89][90][91][92][93][94]. Presently, most, if not all AOPs for steatosis in AOP-Wiki identify a NR or another TF as the MIE.…”
Section: Consistency Of Identified Difld Mechanisms With Current Adve...mentioning
confidence: 99%
“…On the other hand, mixtures of chemicals with different modes of action are usually characterized by the independent action (IA) model (Cedergreen et al, 2008). However, it was shown that even binary and ternary mixtures of compounds with dissimilar modes of action induced triglyceride accumulation in a CA manner (Alarcan et al, 2022). In practice, CA model which generates more conservative predictions is usually the default recommended model for risk assessment (Cedergreen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The project strongly relied on adverse outcome pathways (AOP) and thus in turn substance interactions such as for example the ability of a test compound to interact with certain molecular targets and exert toxicological effects. As a consequence mixture selection in “EuroMix” was essentially based on the toxicodynamic properties of the individual test chemicals (Alarcan et al 2021 ; Beronius et al 2020 ). This is also further substantiated in the recent European Food Safety Authority (EFSA) Mixtox Guidance (EFSA 2021 ).…”
Section: Introductionmentioning
confidence: 99%